Follow up of a randomised trial of two different courses of dexamethasone for preterm babies at risk of chronic lung disease. Issue 2 (1st March 2002) - Armstrong, D L; Penrice, J; Bloomfield, F H; Knight, D B; Dezoete, J A; Harding, J E
Abstract : Objectives: To report 18 month outcome of a randomised trial of two courses of dexamethasone to prevent chronic lung disease of prematurity. Study design: Babies of birth weight 1250 g or less ventilated at 7 days of age were randomised to a 42 day reducing course (long) or a 3 day pulsed (pulse) course of dexamethasone. Growth, cardiovascular status, and respiratory and neurodevelopmental outcomes were assessed at 18 months. Results: Seventy six babies were enrolled. Nine died and three were lost to follow up. Babies receiving the long course were weaned off oxygen more quickly than those receiving the pulse course (47% v 69% on oxygen at 28 days; p = 0.01), but there were no differences in 18 month outcomes. However, children averaged −1 SD for growth parameters, half had moderate or severe disability, and 35% and 19% respectively required oxygen at 36 weeks and discharge. Conclusions: The dexamethasone course used did not influence long term outcome. However, entry criteria for this study selected a group of babies at high risk of poor long term outcome.